Long‐term outcomes of bone augmentation on soft and hard‐tissue stability: a systematic review. Issue 11 (September 2015) - Lutz, Rainer; Neukam, Friedrich W.; Simion, Massimo; Schmitt, Christian M.
Abstract: Background: Peri‐implant hard‐tissue augmentation is a widely used clinical procedure. Aim: The present review aimed to analyse the current literature regarding medium‐ and long‐term data concerning the stability of peri‐implant tissues after hard‐tissue augmentation prior or immediately with implant placement. Material and methods: An electronic literature search was performed using Medline (PubMed) databases detecting clinical studies focusing on hard‐ and soft‐tissue stability around dental implants placed either in augmented alveolar ridges or simultaneously with peri‐implant bone grafting. The search was limited to articles published between 1995 and December 2014, focusing on clinical studies with a prospective study design assessing peri‐implant bone and soft tissue stability over time with a minimum follow‐up of 12 months. Recent publications were also searched manually to find any relevant studies that might have been missed using the search criteria noted above. Results: Thirty‐seven articles met the inclusion criteria and were included in this systematic review. Since the outcome measures and methods, as well as types of grafts and implants used were so heterogeneous, the performance of meta‐analysis was impossible. The highest level of evidence was achieved by randomized clinical trials. Conclusion: Different hard‐tissue augmentation procedures seem to show stable peri‐implant tissues, although, up to now, long‐term stability of the augmented buccal bone is assessed by only few studies. Further research should concentrate on combining three‐dimensional radiographic data with non‐invasive methods as digital surface measuring techniques or ultrasound evaluation.